ARBITRATION CLAUSE AND NULL CONTRACTS: AUTONOMY OF THE ARBITRATION CLAUSE AND THE FAVOR CONTRACTUS PRINCIPLE - Glitz, Frederico Eduardo Zenedin (2010)
This presentation aims the study of an important issue related to arbitration: the arbitration clause and the principle of separability. Firstly, it’s necessary to identify the principle and its peculiarities, the reason for existence, and its function. Then, favor contractus principle, a subject quite discussed by contemporary practices, will be approached. The valid arbitration clause inserted into a null contract is discussed with theoretical and practical arguments. As a conclusion, the prevalence of the separability is reached. In a practical case, the arbitration clause shall prevail and the discussions shall be settled by arbitration procedure.